Tingkat Keunggulan Semen Cair Sapi Simental Dengan Media Penyimpanan Menggunakan Suhu Termos Es Batu - Alfian F Atma (Musamus Journal of Livestock Science, 2023)
This study aims to determine the difference in the quality of liquid semen of Simental cattle using CEP-3 diluent (Bovine Serum Albumin (BSA) in CEP-2 diluent is replaced with 0.4% egg white) and tris aminomethane egg yolk without raffinose stored in a filled thermos. ice. The research was conducted at the Integrated Laboratory of the Faculty of Animal Husbandry and Fisheries, Lamongan Islamic University. The research material was cement of simental cattle. The research used an experimental method, namely 2 treatments and 4 replications consisting of P1 (CEP-3 + 20% egg yolk) and P2 (tris aminomethane without raffinose + 30% egg yolk). The variables observed were motility, spermatozoa membrane integrity and total motile spermatozoa. Data were analyzed using the unpaired T test, total motile spermatozoa were tested using Pearson's Chi Square with an expected value of 40 million motile spermatozoa/ml. The results showed that the P1 and P2 diluent treatments were not significantly different (p>0.05) on spermatozoa motility, but were significantly different (p<0.05) on the 4th and 6th hcrossour storage time on the integrity of the spermatozoa membrane stored in thermos media. fill with ice cubes. The conclusion of the research is that the diluent CEP-3 and tris aminomethane egg yolk without raffinose have the same ability to maintain the quality of liquid semen of simental cattle stored in a thermos filled with ice cubes.